2016
DOI: 10.1007/s11606-016-3928-3
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of the Chronology of Present Illness: Restructuring the HPI to Improve Physician Cognition and Communication

Abstract: BACKGROUND: Patient history-taking is an essential clinical skill, with effects on diagnostic reasoning, patient-physician relationships, and more. We evaluated the impact of using a structured, timeline-based format, the Chronology of Present Illness (CPI), to guide the initial patient interaction. OBJECTIVE: To determine the feasibility and impact of the CPI on the patient interview, written notes, and communication with other providers. DESIGN: Internal medicine residents used the CPI during a 2-week night-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Comparing archetypal examples of narrative and chronologic oncology histories, respondents preferred the chronologic format, confirming pilot work. 27 The chronologic history was preferred for both preparation for a visit with an unknown patient (66% preference) and for preparing one's own note (77% preference). The chronologic summary was preferred in four of the five measured attributes, whereas the narrative summary was favored for thoroughness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing archetypal examples of narrative and chronologic oncology histories, respondents preferred the chronologic format, confirming pilot work. 27 The chronologic history was preferred for both preparation for a visit with an unknown patient (66% preference) and for preparing one's own note (77% preference). The chronologic summary was preferred in four of the five measured attributes, whereas the narrative summary was favored for thoroughness.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 A pilot intervention study using the CPI showed improvements in the clarity of both written notes and verbal sign-out and more efficient sign-out. 27 Interest has risen in structuring a CPI within the EHR. One EHR vendor (Epic) has embedded a chronologic oncology documentation system that allows quasistructured documentation of care events labeled with locally specified categories (eg, surgery, diagnostic imaging, and systemic therapy).…”
Section: Introductionmentioning
confidence: 99%
“…These are critical components in any meaningful learning experience in medicine 3,9 . Examples of educational interventions that promote self‐regulation and positive interprofessional relationships include “Best and Worst Days” case discussions, use of Skeff’s “Chronology of the Present Illness” framework, and autonomy‐supportive changes to the learning climate 10,31,32 …”
Section: Engaged Learnersmentioning
confidence: 99%
“…The emphasis on teaching clinical reasoning skills in many medical schools and residency programs has declined in recent years, 1-6 and several national trends in the current health care environment may be responsible: mounting economic pressures have pushed many health systems and providers to increase clinical productivity and efficiency, 6-11 widespread adoption of electronic health records has increased time spent interfacing with computers instead of patients, 12-14 and a climate has developed in medical schools emphasizing the achievement of high United States Medical Licensing Examination (USMLE) Step scores 15 —all of which have come at the cost of sacrificing time dedicated to teaching clinical skills and diagnostic reasoning. 15-17…”
Section: Declining Emphasis On Clinical Reasoning Skills: a Worrisome...mentioning
confidence: 99%